2021
DOI: 10.1186/s12916-021-02032-2
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and baseline determinants of seropositivity and reinfection rates in health care workers up to 12.5 months after COVID-19

Abstract: We assessed the duration and baseline determinants of antibody responses to SARS-CoV-2 spike antigens and the occurrence of reinfections in a prospective cohort of 173 Spanish primary health care worker patients followed initially for 9 months and subsequently up to 12.5 months after COVID-19 symptoms onset. Seropositivity to SARS-CoV-2 spike and receptor-binding domain antigens up to 149–270 days was 92.49% (90.17% IgG, 76.3% IgA, 60.69% IgM). In a subset of 64 health care workers who had not yet been vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…Recent populationbased studies during the pandemic showed that smoking is a major factor associated with lower response to the SARS-CoV-2 vaccine [45]. Other recent studies showed that smokers had lower antibody titers, suggesting an impaired humoral response [46][47][48]. Our results contribute to the above evidence and show that smoking is a significant negative factor for impaired humoral immunity in vaccinated cancer patients.…”
Section: Discussionsupporting
confidence: 75%
“…Recent populationbased studies during the pandemic showed that smoking is a major factor associated with lower response to the SARS-CoV-2 vaccine [45]. Other recent studies showed that smokers had lower antibody titers, suggesting an impaired humoral response [46][47][48]. Our results contribute to the above evidence and show that smoking is a significant negative factor for impaired humoral immunity in vaccinated cancer patients.…”
Section: Discussionsupporting
confidence: 75%
“…We followed up a total of 445 health care workers (HCW, n=353 from hospital [6] and n=92 from primary care [7] ) in Barcelona, Spain, with different histories of prior COVID-19 exposure. Venous or finger prick blood was collected at different time points before and after immunization with the mRNA-1273 (Spykevax) [1] or the BNT162b2 (Comirnaty) [8] , products from Moderna Biotech and Pfizer-BioNTech, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…An early study reported a rapid rise and subsequent fall of antibodies, which stabilized at later time points, indicating that immunity against SARS-CoV-2 lasted for at least four months after infection 7 . Two later studies extended this protection up to at least six months 8,2 , while recent estimates venture that it persists for at least a year 9,10 . However, knowledge of the kinetics and nature of the immune response to SARS-CoV-2 infection is still limited, and larger longitudinal studies are needed to define the half-life of antibodies against SARS-CoV-2 and their respective kinetics.…”
Section: Introductionmentioning
confidence: 98%